Hyperandrogenemia and high prolactin in congenital utero-vaginal aplasia patients - Oppelt, Patricia; Mueller, Andreas; Stephan, Liana; Dittrich, Ralf; Lermann, Johannes; Büttner, Christian; Ekici, Arif Bülent; Conzelmann, Gabi; Seeger, Harald; Schoeller, Dorit; Rall, Katharina; Beckmann, Matthias; et al. (Reproduction, 2017)
Patients with the Mayer-Rokitansky-Küster-Hauser syndrome (MRKH) have a congenital utero-vaginal cervical aplasia, but normal or hypoplastic adnexa and develop with normal female phenotype. Some reports mostly demonstrated regular steroid hormone levels in small MRKH cohorts including single MRKH patients with hyperandrogenemia and a clinical presentationof hirsutism and acne has also been shown. Genetically a correlation of WNT4 mutations with singular MRKH patients and hyperandrogenemia was noted. This study analyzed the hormone status of 215 MRKH patients by determining the levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), estradiol, 17-OH progesterone, testosterone, dehydroepiandrosterone sulfate (DHEAS), sex hormone-binding globulin (SHBG) and prolactin to determine the incidence of hyperandrogenemia and hyperprolactinemia in MRKH patients. Additional calculations and a ratio of free androgen index and biologically active testosterone revealed a hyperandrogenemia rate of 48.3%, hyperprolactinemia of 9.8% and combined hyperandrogenemia and hyperprolactinemia of 4.2% in MRKH patients. The rates of hirsutism, acne and especially polycystic ovary syndrome (PCOS) were in the normal range of the population and showed no correlation with hyperandrogenemia. A weekly hormone assessment over 30 days comparing 5 controls and 7 MRKH patients revealed high androgen and prolactin, but lower LH/FSH and SHBG levels with MRKH patients. The sequencing of WNT4, WNT5A, WNT7A and WNT9B demonstrated no significant mutations correlating with hyperandrogenemia. Taken together, this study shows that over 52% of MRKH patients have hyperandrogenemia without clinical presentation and 14% hyperprolactinemia, which appeals for general hormone assessment and adjustments of MRKH patients.
EVALuna2:9378